Epidemiology and Knowledge of First Aid Treatment Related to Burn Injury in the Rural Region of Kulon Progo, Indonesia - Ramli, Rianto Noviady; Prawoto, Almas; Riasa, Nyoman Putu; Saputro, Iswinarno Doso; Mas’ud, Ahmad Fawzy (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: We investigated the epidemiology and the knowledge of first aid regarding to burns in the rural area of Kulon Progo, located in Indonesia. Although 44% of Indonesia’s population resides in rural areas, data of burn in Indonesia are very limited to national referral centers located in Indonesia’s largest cities. We also surveyed the patients and families of these burn patients to try to understand their knowledge on the first aid of burns. AIM: We wanted to explore and discover what myths and misperceptions existed in rural communities. MATERIALS AND METHODS: A retrospective study analyzing the medical records of patients with burns admitted to two of Kulon Progo’s largest referral hospitals between January 2018 and December 2019. A survey was distributed to the patients and their families regarding their knowledge on the first aid of burns. We wanted to analyze if certain groups of the population were more at risk for specific types of burn etiologies, the correlation between burn etiology and length of stay, the correlation between total body surface area (TBSA) of burns and length of stay in the hospital, and the correlation between education level of survey participants’ and their knowledge of first aid of burns. RESULTS: A total of 115 patients were reviewed in this study. The highest proportion of total burn injuries occurred in the age group of 1–14 years old (38%). The major etiology of all burn cases were caused by scald (54%). Housewives and children were at a higher risk for scalds and laborers were at a higher risk for electrical and chemical burns (p = 0.001). There was no significant correlation between etiology and length of stay (p = 0.29). There was a statistically significant correlation between the TBSA and the length of hospital stay (p = 0.0001). The majority of survey respondents (66%) had poor knowledge on the first aid of burns. There was no significant correlation between education level and knowledge of first aid of burns (p = 0.07547). CONCLUSIONS: Children, laborers, and housewives have a significant risk of suffering from a burn injury. A majority of people still have poor knowledge on the first aid of burns. There was no correlation between education levels and knowledge of first aid burns.